Simultaneous Determination of Loureirin A, Loureirin B and Resveratrol by HPLC in Resina Draconis Tablet - Cheng, Weiming; Yang, Xiaojie; Huang, Qinwei; Shi, Bei; Chen, Huimin; Chen, Bilian (Asian Journal of Chemistry, 2013)
An HPLC method was developed for the simultaneous determination of 3 bioactive components in resina draconis tablet. The solid phase was Agilent Zorbax SB-C18 with glacial acetic acid (1®90)-acetonitrile as the mobile for the gradient elution. The results of the methodology all fit the analytical requests and the recoveries were 101.8, 103.2 and 104.2 % for the 3 targeted components, respectively. It was the first report that figured out the method for the simultaneous determination of bioactive components with different structures in resina draconis tablet by HPLC and simple, accurate and reliable for the quality control of resina draconis tablet.